An empirical study : closeness of association, control and power influence on perceptions of stigmatization following financial misconduct - Aw, Jing Wen (2013)
This study focuses on stigma flow from the responsible individuals to others and investigates the effects of several relationship elements on stigma, between these two parties, following a financial misconduct. The study sets out to confirm the concept of stigma proposed by Link and Phelan [2001]. It also aims to empirically prove that individuals who are closely associated could expect to suffer from a larger amount of stigma. Further, the study also hopes to establish a new model, which builds on existing stigma literature on the effects of controllability. We include power of individuals in an organisation under the same consideration that control could be derived from power, therefore affecting amount of stigma that one could expect to suffer.